Timing of Diapause Initiation and Overwintering Conditions Alter Gene Expression Profiles in Megachile rotundata - Cambron-Kopco, Lizzette D.; Yocum, George D.; Yeater, Kathleen M.; Greenlee, Kendra J. (Frontiers in Physiology, 2022)
Within the United States and Canada, the primary pollinator of alfalfa is the alfalfa leafcutting bee (ALCB), Megachile rotundata. Our previous findings showed that overwintering conditions impacted gene expression profile in ALCB prepupae that entered diapause early in the season. However, ALCB are a bivoltine species, which begs the question of whether bees entering diapause later in the season also show this trend. To better understand the effects of the timing of diapause initiation, we analyzed mRNA copy number of genes known to be involved in diapause regulation in early- and late-season diapausing ALCB that were overwintered in field conditions or using current agricultural management conditions. We hypothesized that overwintering conditions for late diapausing bees also affects gene expression profiles. Our results showed that expression profiles were altered by both overwintering condition and timing of diapause initiation, with bees that entered diapause earlier in the season showing different expression patterns than those that entered diapause later in the season. This trend was seen in expression of members of the cyclin family and several targets of the insulin signaling pathway, including forkhead box protein O (FOXO), which is known to be important for diapause regulation and stress responses. But, of the genes screened, the proto-oncogene, Myc, was the most impacted by the timing of diapause initiation. Under field conditions there was significant differences in Myc expression between the early and late season samples in all months except for November and February. This same general trend in Myc expression was also seen in the laboratory-maintained bees with significant difference in expression in all months except for November, February, and May. These results support previous conclusions from our research showing that the molecular regulation of diapause development in ALCB is not a simple singular cascade of gene expression but a highly plastic response that varies between bees depending upon their environmental history.